Development of glazed candied pineapple (Anonas comosus Linn. merr.) - Vigo, Elena B.
A standard process for glazed pineapple (Ananas comosus Linn. merr.) was developed from rare-ripe fruit of the Smooth cayenne variety. From two quick candying methods, the one most suitable for pineapple was selected. The method chosen, which consisted of plumping the fruits in 75° Brix syrup by vacuum pressure for 48 hours gave a product which is more acceptable in color and flavor than the other method which involved plumping the fruits in 40° Brix syrup by cabinet drying for 24 hours. Syrups with different proportions of sucrose to glucose, namely 1:2, 1:1 and 2:1 were tried. Objective tests and microbiological examinations for yeasts and molds and sensory evaluation conducted during storage for one month at room temperature showed that the 2:1 proportion gave the more acceptable product and exhibited the longest shelf-life. The candied fruits were glaced using 1.5%, 2.0% and 2.5% pectin concentrations. A 20% glucose was mixed with the different pectin solutions. The 2.0% and 2.5% pectin concentrations produced the best glaced product with the following characteristics: glossy and dry; not sticky; and firm and tender. Considering the economic aspect, the 2.0% pectin was chosen.